Issue of halal certification at hotel in Malaysia / Nur Ain Ismail and Kasma Norhasrianti Mohamed Arifin - Ismail, Nur Ain; Mohamed Arifin, Kasma Norhasrianti (2020)
The main objective of this study is to investigate the issue of Halal Certification at hotel in Malaysia. Most hoteliers do not bother in obtaining the Halal Certification (Sabidin, 2015) and lack of enforcement by Department of Islamic Development Malaysia (JAKIM) and monitoring Halal Logo. This research was done using secondary studies which is argumentative method. In this study, there are three issues that found related with the topic. The first issue of Halal Certification at hotel in Malaysia is lack of enforcement JAKIM in monitoring the usage of Halal Logo. It can be proven by issue related Ramadan Buffet in hotel. Second issue are application of Halal Certification which is voluntary, so they have own choice whether to apply Halal Certification or not. They apply Halal Certification because to avoid doubt and as a marketing tools to attract especially the Islamic customers. However, some of hotels did not want to apply Halal Certification because the fees to apply Halal Certification are expensive. The third issue is cancellation of Halal Certification which is does not meet the standard. This is because the operator hotel did not follow the requirement after getting Halal Certification for example the hotel changes the supplier without informing State Islamic Religious Department (JAIN). So, the conclusion regarding this issue is consumers more aware about seek Halal Certification in food establishment. This study future researchers can continue this study not only focusing on hotels specifically on the food premise but also find out the reason why Halal Certification is not obtained in the others departments.